Impact of nest relocation on the reproductive success of Loggerhead Turtles, Caretta caretta, in the Göksu Delta, Turkey (Reptilia: Cheloniidae). Issue 1 (2nd January 2018) - Candan, Onur
Abstract : When the nests of marine turtles are at a risk of inundation, relocation of the nests are often used in the conservation measures. Here, I determined the effect of nest relocation on Loggerhead Turtle ( Caretta caretta ) egg hatching success during the 2013 and 2014 nesting seasons in the Göksu Delta, Mersin, Turkey. I compared natural and relocated clutches, including those relocated before and after inundation, and evaluated 102 (94.6%) and 63 (81.1%) of survived nests in 2013 and 2014 respectively. Relocated nests experienced a 30% decrease in hatching success and a more prolonged incubation period compared to nests left in situ . Egg failure in nests relocated before and after inundation was similar in early-stage embryos, whereas it was three-fold higher in mid-stage embryos and two-fold lower in late-stage embryos. Thus, there was no significant difference in overall hatching success between the two relocation types. Moreover, there was no effect of delayed relocation of nests after inundation on hatching success. Possible impacts specific to the nesting site should be considered and explored before using nest relocation as a conservation tool. The relocation approach is recommended for nests at a high risk of inundation when the loss of nests is inevitable.